ANALYZING THE CHARACTERISTICS AND BIOLOGICAL ACTIVITIES OF METHANOLIC EXTRACTS FROM STACHYS BYZANTINE LEAVES - Ali Q. Khazaal; Zainab F. Mahmood; Sanaa A. Hammood (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to examine the suppressive effects of Stachys byzantine leaf methanolic extracts on cancer cell lines and pathogenic microbes. Five concentrations of S. byzantine methanolic extract, from 25 to 400 µg/ml, were applied to HepG1 and HCT116 cells. S. byzantine methanolic extracts inhibited liver and colon cancer cell viability at different concentrations. The MTT assay results demonstrated that the extract’s IC-50 values for HepG1 were 271.61µg/ml and for HCT116 was 184.86µg/ml. The methanolic extracts obtained from S. byzantine showed antibacterial activity against Gram-negative and Gram-positive bacteria. The extract inhibited Staphylococcus aureus with 15, 20, and 22 mm inhibition zones at 100, 200, and 400 mg/ml, respectively. However, the extract was more effective against Pseudomonas aeruginosa, with inhibitory zones of 30, 30, and 35 mm at 100, 200, and 400 mg/ml respectively. This study indicates that methanolic extracts derived from S. byzantine leaves have anti-cancer and antibacterial properties.